Relativistic X-Ray Reflection Models for Accreting Neutron Stars - Garcia, Javier A.; Dauser, Thomas; Ludlam, Renee; Parker, Michael; Fabian, Andrew; Harrison, Fiona A.; Wilms, Jörn (Astrophysical Journal, 2022)
We present new reflection models specifically tailored to model the X-ray radiation reprocessed in accretion disks around neutron stars, in which the primary continuum is characterized by a single-temperature blackbody spectrum, emitted either at the surface of the star or at the boundary layer. These models differ significantly from those with a standard power-law continuum, typically observed in most accreting black holes. We show comparisons with earlier reflection models and test their performance in the NuSTAR observation of the neutron star 4U 1705-44. Simulations of upcoming missions such as XRISM-Resolve and Athena X-IFU are shown to highlight the diagnostic potential of these models for high-resolution X-ray reflection spectroscopy. These new reflection models xillverNS, and their relativistic counterpart relxillNS, are made publicly available to the community as an additional flavor in the relxill suite of reflection models.
CRIS-Team WoS Importer:2022-02-18